Direito e saúde na tríplice fronteira: o município de Foz do Iguaçu, analisado a partir das relações entre o direito e a política pública estratégia saúde da família - Oliveira, Ana Flávia Machado de (2021)
The main objective of this study was to analyze the peculiarities of public health in the region of Foz do Iguaçu – PR, a city that integrates the triple border Brazil – Argentina – Paraguay. Therefore, the starting point was the concept of health and its evolution in Brazil, following the historical path until the promulgation of the Federal Constitution of the Republic of 1988, in which, through article 196, it determined that health would become a right of all and the State's duty, guaranteed through social and economic policies aimed at reducing the risk of illness and other diseases and at universal and equal access to actions and services for its promotion, protection and recovery. Afterwards, the main means of effecting this right was analyzed: public policies. Then, to detail the chosen public health policy: The Family Health Strategy - ESF (formerly the Family Health Program - PSF), analyzing its particularities, especially those that directly impact its effectiveness in the analyzed region. The results of this study were obtained through bibliographic research, consultation of public data on state platforms, in addition to a questionnaire sent to the State Health Department of Paraná and the Municipal Health Department of Foz do Iguaçu. These results pointed to the lack of a thorough look at local conditions and the lack of coordinated and effective confrontation of local problems by the central government, which often, when elaborating public health laws and policies, do not observe the multifaceted Brazilian reality. It is hoped through this study, to bring to light the latent need to observe local peculiarities in the formulation and implementation of public health policies, under penalty of compromising the effective access to the fundamental right to health.